Quality of Health Care: Informatics Foundations - Hasman, A.; Safran, C.; Takeda, H. (Methods of Information in Medicine, 2003)
Objective: To discuss in what ways computer systems can contribute to the quality of healthcare and on which principles of informatics successful systems are based.Methods: Part of the information was obtained via a literature search and part is based on the knowledge of the authors.Results: The results of the literature search are reported. The answers to the questions whether decision support is useful and which factors determine its success, the foundations of computerized guidelines systems and applications of physician order entry and medical risk management are presented. Conclusions: Despite many publications concerning diagnostic support systems their use in clinical practice is limited. Reminder systems do appear to have an impact on health outcomes. Standards for guideline models are being developed for effective sharing of guidelines across systems. Electronic patient records and physician order entry systems are useful aids in medical risk management.
Keywords: Literature review; decision support; risk management; computerized guideline systems; guideline models; physician order entry systems; decision support methods